Social presence and cognitive presence in an online training program for teachers of Portuguese: relation and methodological issues - Jorge, Idalina (2013)
Designing activities based on dialogue, such as forums, encouraging interaction between the tutor and the students and among students has proved to influence positively on students’ motivation, sense of community and engagement (Jorge, 2001; Jorge, 2006). Social presence has been defined as the participants’ ability to project both socially and emotionally (Rourke et al., 2001); cognitive presence has been defined as the participants’ ability to build knowledge and reflect collaboratively (Garrison et al, 2001). Building on the community of inquiry model (Garrison & Anderson, 2003), a research was conducted to relate social and cognitive presence, and verify on which dimensions of both variables the correlation was more evident. The teacher training program Navegar no Português (Sailing in Portuguese) was a nationwide project to improve the scientific, didactic and computer skills of the teachers involved. More than 200 teachers, both tutors and students, were organized in 11 regional teams. This research was designed to assess social and cognitive presence in eleven online forums. Correlations among dimensions of social and cognitive presence were established, in order to detect if or how social presence is correlated to cognitive presence. The association between cognitive and social presence only shows evident at the phases of exploration and integration of the first. In fact, in triggering and resolution messages, social utterances hardly occur. The analysis of significance value associated with chi-square test finds that there is a relationship and dependence between these two variables. The degree of association proves significant, though not very intense. The stage of exploration shows a higher correlation with connectivity and self-disclosure, being both functions represented in a balanced manner. Results don´t indicate that greater interactivity was associated with higher levels of reflexivity. My data also show that the types of self-disclosure and connectivity increase when the cohesive decrease. The first is associated with early stages of discussion. Once these phases are overcome, relations stabilize at a level of respect and mutual acceptance and students are more focused on cognitive goals.